Impact of railway noise on student concentration in classroom learning: An environmental and educational perspective - Mahardika, Tesar; Widodo, Sugeng (Journal of Environment and Geography Education, 2025)
Background: Environmental noise pollution, particularly from railway activities, poses a significant challenge to student concentration and learning effectiveness. This study investigates the correlation between railway noise levels and student concentration in classroom learning within an environmental education framework. Method: The method used in this study is descriptive quantitative. The population in this study were all fifth-grade students of State Elementary School 1 Rajabasa Raya totaling 98 students. The sample of this study was 78 respondents. Findings: The results of the study regarding the intensity of noise measured have exceeded the threshold value (nab). While the results of the product moment correlation analysis method, there is a relationship between train noise and student learning concentration at State Elementary School 1 Rajabasa Raya with a value of p = 0.000 (p <0.005). Conclusion: Persistent railway noise has a measurable adverse effect on student learning concentration, emphasizing the need for environmental education-based mitigation strategies. Novelty/Originality of this article: This study contributes to the field of environmental education by integrating noise pollution analysis with student learning outcomes. It highlights the necessity of soundproofing measures, school infrastructure adjustments, and adaptive learning strategies to minimize the impact of environmental noise on education.